2010
DOI: 10.1073/pnas.1002178107
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 4 (Nox4) is a major source of oxidative stress in the failing heart

Abstract: NAD(P)H oxidases (Noxs) produce O 2 − and play an important role in cardiovascular pathophysiology. The Nox4 isoform is expressed primarily in the mitochondria in cardiac myocytes. To elucidate the function of endogenous Nox4 in the heart, we generated cardiac-specific Nox4 −/− (c- Nox4 −/− ) mice. Nox4 expression was inhibited in c- Nox4 −/− mice in a heart-specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
567
8
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 678 publications
(608 citation statements)
references
References 30 publications
29
567
8
4
Order By: Relevance
“…As reported, Nox2 and Nox4 are expressed in cardiomyocytes and myocardial fibroblasts, and their activation plays an important role in myocardial hypertrophy and/or cardiac remodeling. 29,30 In general, Nox-derived ROS production activates redox-sensitive signaling pathways and stimulates the transcription of hypertrophy-related genes, eventually resulting in cardiac hypertrophy. 31 In this study, a dose-dependent elevation of ROS production was detected in NRCMs after treatment with IS, and a remarkable increase in ROS level in the myocardial tissue was also observed in mice treated with IS (100 mg/kg per day) for 8 weeks (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…As reported, Nox2 and Nox4 are expressed in cardiomyocytes and myocardial fibroblasts, and their activation plays an important role in myocardial hypertrophy and/or cardiac remodeling. 29,30 In general, Nox-derived ROS production activates redox-sensitive signaling pathways and stimulates the transcription of hypertrophy-related genes, eventually resulting in cardiac hypertrophy. 31 In this study, a dose-dependent elevation of ROS production was detected in NRCMs after treatment with IS, and a remarkable increase in ROS level in the myocardial tissue was also observed in mice treated with IS (100 mg/kg per day) for 8 weeks (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…109 Since this report, several other studies have demonstrated a critical role of NOX4 in fibrosis involving the liver, 110 kidney, 111 and heart. 112 More recent studies demonstrate that the up-regulation of NOX4 is coupled to Nrf2 induction, and this adaptive response is critical to apoptosis susceptibility of myofibroblasts and resolution of fibrosis in young mice. 2 In contrast, in aged mice, there is impaired Nrf2 activation leading to an altered NOX4-Nrf2 redox balance and acquisition of an apoptosis-resistant myofibroblast phenotype resulting in persistent fibrosis.…”
Section: Nrf2 In Aging and Lung Fibrosismentioning
confidence: 99%
“…Oxidative stress products such as superoxide radical (O 2 -) and hydroxyl radical (-OH) can attack the cell membrane and further lead to tissue oxidative injury (Mak et al, 2002). Nox4, as the important Nox isoform expressed in the heart, has been acknowledged as the principal source of oxidative stress, which can also mediate myocardial apoptosis (Kuroda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%